Computational Speciation Models: A Tool for the Interpretation of Spectroelectrochemistry for Catalytic Layers under Operative Conditions. Issue 11 (11th August 2017) - Montegrossi, G.; Giaccherini, A.; Berretti, E.; Benedetto, F. Di; Innocenti, M.; d'Acapito, F.; Lavacchi, A.
Abstract : In this study, the first coupled FEXRAV and chemical speciation modelling study of the Pd deactivation is presented. Due to the high brilliance of synchrotron light, FEXRAV can investigate deeply buried surfaces. More specifically, we directly analyzed the evolution of the Pd/C catalytic layer during a voltammetric cycle, through a specifically designed electrochemical cell. Still, we observed a complex interfacial chemistry of Pd, which impairs a straightforward interpretation of FEXRAV data. Exploiting thermodynamic chemical speciation modelling we were able to overcome this issue. The study leads to three main results: 1) the confirmation of the relationship between the change of the Pd/Pd(II) ratio and the change of the Fluorescence intensity 2) the investigation of the deactivation mechanism 3) the identification of the relevant species leading to the electrodissolution of Pd under operative conditions. This study opens new perspectives for the application of the chemical speciation modelling to the study of the deactivation mechanism of Pd in Pd/C catalytic layers under operative conditions in different electrolytes.